The DnaE polymerase from Deinococcus radiodurans features RecA-dependent DNA polymerase activity. Issue 6 (5th December 2016) - Randi, Lorenzo; Perrone, Alessandro; Maturi, Mirko; Dal Piaz, Fabrizio; Camerani, Michela; Hochkoeppler, Alejandro
Abstract : We report in the present study on the catalytic properties of Deinococcus radiodurans DnaE polymerase, whose DNA elongation efficiency was compared with the homologous Escherichia coli polymerase. Contrary to the latter, the deinococcal enzyme was found to be strictly dependent on RecA recombinase. Abstract : We report in the present study on the catalytic properties of the Deinococcus radiodurans DNA polymerase III α subunit (αDr). The αDr enzyme was overexpressed in Escherichia coli, both in soluble form and as inclusion bodies. When purified from soluble protein extracts, αDr was found to be tightly associated with E. coli RNA polymerase, from which αDr could not be dissociated. On the contrary, when refolded from inclusion bodies, αDr was devoid of E. coli RNA polymerase and was purified to homogeneity. When assayed with different DNA substrates, αDr featured slower DNA extension rates when compared with the corresponding enzyme from E. coli ( E. coli DNA Pol III, αEc), unless under high ionic strength conditions or in the presence of manganese. Further assays were performed using a ssDNA and a dsDNA, whose recombination yields a DNA substrate. Surprisingly, αDr was found to be incapable of recombination-dependent DNA polymerase activity, whereas αEc was competent in this action. However, in the presence of the RecA recombinase, αDr was able to efficiently extend the DNA substrate produced by recombination. Upon comparing the rates of RecA-dependent and RecA-independent DNA polymerase activities, we detected a significant activation of αDr by the recombinase. Conversely, the activity of αEc was found maximal under non-recombination conditions. Overall, our observations indicate a sharp contrast between the catalytic actions of αDr and αEc, with αDr more performing under recombination conditions, and αEc preferring DNA substrates whose extension does not require recombination events.